PENEGAKAN HUKUM TERHADAP WARGA NEGARA ASING (WNA) YANG MELANGGAR IZIN TINGGAL (OVERSTAY) - Pigayanti, Ni Putu; Saputra, Komang Edy Dharma; Suryana, Kadek Dedy (CV Widina Media Utama, 2023)
The objectives of this study include the regulation of foreigners' residence permits in Indonesia based on the Law on Immigration and how sanctions for foreigners who violate residence permits in Indonesia or what is commonly called Overstay. This research uses descriptive normative method. The results of this study are “Immigration is a matter of traffic in people entering or leaving the territory of the Republic of Indonesia and Supervision of foreigners in Indonesia.” Referring to the Immigration Law, there are two important regulatory elements, namely 1) regulations regarding all matters relating to the traffic of people leaving and entering and staying in the territory of the Republic of Indonesia, 2) regulations relating to all matters concerning the supervision of foreigners in the territory of Indonesia. Sanctions that can be implemented for cases of foreign nationals (WNA) who violate the abuse of residence permits are in the form of administrative immigration sanctions (TAK) or criminal sanctions. Administrative sanctions are sanctions given by immigration officials to foreigners outside of the judicial mechanism. While criminal sanctions are a mechanism that runs on a network where there is involvement from law enforcement.ABSTRAKTujuan penelitian ini meliputi pengaturan izin tinggal WNA di Indonesia berdasarkan Undang-Undang tentang Keimigrasian dan bagaimana sanksi bagi WNA yang melanggar izin tinggal di Indonesia atau yang biasa di sebut dengan Overstay. Penelitian ini menggunakan metode deskriptif normative. Hasil dari penelitian ini yaitu “Keimigrasian adalah hal ihwal lalu lintas orang yang masuk atau keluar wilayah Negara Republik Indonesia dan Pengawasan orang asing di Indonesia.” Mengacu pada UU Keimgirasian ada dua unsur aturan penting yaitu 1) aturan mengenai semua hal yang bekaitan dengan lalu lintas dari orang yang pergi dan masuk serta tinggal di wilayah Republik Indonesia, 2) peraturan yang berkaitan dengan segala hal tentang pengawasan untuk orang asing di wilayah Indonesia. Sanksi yang bisa diimplementasikan untuk kasus Warga Negara Asing (WNA) yang melanggar penyalahgunaan izin tinggal yaitu dalam bentuk sanksi administrative keimigrasian (TAK) atau sanksi pidana. Mengenai sanksi administrative yaitu sanksi yang diberikan Pejabat Imigrasi untuk WNA di luar dari mekanisme peradilan. Sedangkan sanksi pidana yaitu sebuah mekanisme yang berjalan pada sebuah jaringan dimana ada keterlibatan dari penegak hukum.